Integrating self-directed learning in facilitating writers engagement through Grammarly: Exploring the perceptions of premium users - Fajriyah Novi Wardatin; Slamet Setiawan; Ali Mustofa; Him’mawan Adi Nugroho (Universitas Merdeka Malang, 2022)
This present study sought to explore the writers’ perceptions toward the use of Grammarly. It also concerned the challenges they might be faced while utilizing the features provided by the system. The descriptive analysis was elaborated with supporting the statistic data from a 6-point Likert scale questionnaire, including the needs of Grammarly use in connection with its advantages and practicality, and also covered three dimensions of self-directed learning, such as self-management, motivation, and self-monitoring. The respondents were twenty-three male and female writers who have experienced subscribing as a premium users. To get a comprehensive investigation, the respondents were required to perceive their views in the form of short comments of open-ended questions. Although most writers viewed positive responses towards the use of Grammarly, two main problems faced during the use of Grammarly were covered on technical issues and un maximum usage of particular features. Interestingly, the writers also considered that the role of teachers could not be replaced despite all the growing technological sophistication and implementation of self-learning, which is currently becoming a relatively dominant need in terms of learning independently. DOI: 10.26905/enjourme.v7i1.6849